The next wave of air-filled fires - Chew, Boon Cheong; Hissamuddin, Muhammad Hafizuddin; Subramonian, Sivarao; Hamid, Syaiful Rizal; Thangaraj, Joseph Sahaya Anand; Chong, Kuan Eng; Rajiani, Ismi (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The air filled tires have been a domain design of the automobile industry for nearly a decade and they appear until today-although they are carrying risks of tires failure which could lead to injuries and death in road accidences. Alternatively, the airless tires have a lot of potential and capable to resolve existing tires deficiencies. However, to date, the airless tires are confined to be used on motorized golf carts or heavy equipment. The objective of this study is to investigate the awareness of Malaysian drivers on both air filled tires and airless tires. Through descriptive quantitative research with the structured interview on100 customers whom were servicing their tires at 20 professional tires shops located at Kuala Lumpur and Selangor, the strengths and weaknesses of air filled tires and airless tires were examined respectively. As a conclusion, the existence of air filled tires and airless tires are two completely different technologies that have their own respective weaknesses that need to be overcome. We strongly believe that airless tire will represents the next step in a long innovation path for tire industry, while the air filled tire, we foresee this technology will continue for a long time to come. By learning from the Blue Ocean Strategy and by understanding the four action framework, we foresee the next wave of air filled tires would bring a revolutionary new tire technology which is beyond the air filled or airless tires narrow classification.